Genetic variation in genes regulating skeletal muscle regeneration and tissue remodelling associated with weight loss in chronic obstructive pulmonary disease. Issue 6 (15th September 2021) - Lakshman Kumar, Preeti; Wilson, Ava C.; Rocco, Alison; Cho, Michael H.; Wan, Emily; Hobbs, Brian D.; Washko, George R.; Ortega, Victor E.; Christenson, Stephanie A.; Li, Xingnan; Wells, J. Michael; Bhatt, Surya P.; et al.
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is the third leading cause of death globally. COPD patients with cachexia or weight loss have increased risk of death independent of body mass index (BMI) and lung function. We tested the hypothesis genetic variation is associated with weight loss in COPD using a genome‐wide association study approach. Methods: Participants with COPD ( N = 4308) from three studies (COPDGene, ECLIPSE, and SPIROMICS) were analysed. Discovery analyses were performed in COPDGene with replication in SPIROMICS and ECLIPSE. In COPDGene, weight loss was defined as self‐reported unintentional weight loss > 5% in the past year or low BMI (BMI < 20 kg/m 2 ). In ECLIPSE and SPIROMICS, weight loss was calculated using available longitudinal visits. Stratified analyses were performed among African American (AA) and Non‐Hispanic White (NHW) participants with COPD. Single variant and gene‐based analyses were performed adjusting for confounders. Fine mapping was performed using a Bayesian approach integrating genetic association results with linkage disequilibrium and functional annotation. Significant gene networks were identified by integrating genetic regions associated with weight loss with skeletal muscle protein–protein interaction (PPI) data. Results: At the single variant level, only the rs35368512 variant, intergenic to GRXCR1 and LINC02383, was associated with weight loss (odds ratio = 3.6, 95% confidence interval = 2.3–5.6, P = 3.2 × 10 −8 ) among AA COPD participants in COPDGene. At the gene level in COPDGene, EFNA2 and BAIAP2 were significantly associated with weight loss in AA and NHW COPD participants, respectively. The EFNA2 association replicated among AA from SPIROMICS ( P = 0.0014), whereas the BAIAP2 association replicated in NHW from ECLIPSE ( P = 0.025). The EFNA2 gene encodes the membrane‐bound protein ephrin‐A2 involved in the regulation of developmental processes and adult tissue homeostasis such as skeletal muscle. The BAIAP2 gene encodes the insulin‐responsive protein of mass 53 kD (IRSp53), a negative regulator of myogenic differentiation. Integration of the gene‐based findings participants with PPI data revealed networks of genes involved in pathways such as Rho and synapse signalling. Conclusions: The EFNA2 and BAIAP2 genes were significantly associated with weight loss in COPD participants. Collectively, the integrative network analyses indicated genetic variation associated with weight loss in COPD may influence skeletal muscle regeneration and tissue remodelling.